3(x-2)+x+4=2(x-1)

Simple and best practice solution for 3(x-2)+x+4=2(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)+x+4=2(x-1) equation:


Simplifying
3(x + -2) + x + 4 = 2(x + -1)

Reorder the terms:
3(-2 + x) + x + 4 = 2(x + -1)
(-2 * 3 + x * 3) + x + 4 = 2(x + -1)
(-6 + 3x) + x + 4 = 2(x + -1)

Reorder the terms:
-6 + 4 + 3x + x = 2(x + -1)

Combine like terms: -6 + 4 = -2
-2 + 3x + x = 2(x + -1)

Combine like terms: 3x + x = 4x
-2 + 4x = 2(x + -1)

Reorder the terms:
-2 + 4x = 2(-1 + x)
-2 + 4x = (-1 * 2 + x * 2)
-2 + 4x = (-2 + 2x)

Add '2' to each side of the equation.
-2 + 2 + 4x = -2 + 2 + 2x

Combine like terms: -2 + 2 = 0
0 + 4x = -2 + 2 + 2x
4x = -2 + 2 + 2x

Combine like terms: -2 + 2 = 0
4x = 0 + 2x
4x = 2x

Solving
4x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
4x + -2x = 2x + -2x

Combine like terms: 4x + -2x = 2x
2x = 2x + -2x

Combine like terms: 2x + -2x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 2(1-11n)+11=-8(n+1)-7 | | -4x+7=27 | | -2a+40+9a=4a-7a | | x^2*5y^4= | | 4(3y+-1)+13=5y+2 | | 6b=6 | | x^2*5y^2= | | 7[200]+12x=1736 | | 2.5x+2=4x+5 | | 4(3y-10)+13=5y+2 | | x^3-8x-6=0 | | 15x-4=2x+9 | | x+10=x | | 4ax^4-22ax^2+10a= | | 2x+5+7x=32 | | -5x+x+3=-13 | | 14=8x+2y | | -(3+4)=6z-3(3z+2) | | 0=16t^2-96t-112 | | 15-(x-2)= | | -12(6x+9)=-6(x+7) | | -3(-2y+3)-(4y-3)+5y+9= | | 6(2x-3)-8x=4x-2 | | 12x+7+x=20 | | 15=15-7c | | -3(2x-4)+8x-4= | | 4a^2-21a+5= | | (3*6/2)v+10=9v+9 | | 12x-10=-6x+14 | | 2m=-18-5 | | 2m=-12-5 | | -5x-18=-268 |

Equations solver categories